Dynamic Contact Angle and Corrosion Test Measurements on Cu and CuO-Stearic Acid Modifications on Steel Surfaces - Iwan Setiawan; Satria Robi Trisnanto; Ika O Suryani (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2020)
In this study, a copper (Cu) coated steel surface’s dynamic contact angle and corrosion rate was compared to the bare steel and stearic acid modified surfaces. Various steps of surface treatment have been performed including electrodeposition of Cu, CuO formation from H2O2 immersion with stearic acid modification to obtain dynamic contact angle and the corrosion rate data. The Cu-coated steel’s dynamic contact angle was increased as it implied the surface after Cu treatment was more hydrophilic than the bare steel, with sliding angle and contact angle hysteresis of 54.9o ± 2.39o and 39.5o ± 1.91o, respectively. However, corrosion test measurements by using a mass loss method to quantify the corrosion rate showed that Cu-coated steel and stearic acid-modified Cu-O coated steel had no remarkable difference in corrosion rate. It was found that the Cu-coated steel and stearic acid-modified Cu-O coated steel had corrosion rate eight times slower than the bare surface.